Pengembangan Perangkat Pembelajaran Berbasis Proyek Materi Zakat, Infaq, Sedekah, dan Wakaf terhadap Hasil belajar pada Mata Kuliah Pendidikan Agama Islam Fakultas Ekonomi dan Bisnis Universitas Negeri Gorontalo - Kholid Mootalu; Agil Bahsoan; Muhammad Fakhri Mudi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2026)
This study aims to develop a learning device that integrates a project-based approach on the topic of Zakat, Infaq, Sedekah, and Wakaf (ZISWAF) in the Islamic Education. The method used in this study is Research and Development (R&D) analysis, which includes the stages of needs, device design, validation by experts, product revision, limited trials, and small-scale implementation. The results of the study obtained The validity of the learning device was obtained through expert assessment, resulting in a validity percentage of 88.26% with the criteria "Valid". The practicality of the learning device is seen from the implementation of learning which reaches 90% and gets a positive response from students during the learning process. Meanwhile, the effectiveness of the device is measured through the increase in student learning outcomes as indicated by the increase in student Pre-test and Post-test scores. These results indicate that the developed learning device meets the criteria of valid, practical, and effective for use in the learning process. Thus, this project-based learning device has proven effective in encouraging the creation of meaningful, collaborative, and contextual learning at the higher education level